DEVELOPMENT MODEL FOR SUPPORTING THE ACCOMPLISHMENT OF ACADEMIC LEVEL: CASE STUDY OF BINA NUSANTARA UNIVERSITY - Heripracoyo, Sulistyo; Saputra, Wawan; Wince, Wince (CommIT (Communication and Information Technology) Journal, 2013)
The fact that a small number of lecturers who are able to meet or pass the requirementsfor obtaining or enhancing the academic hierarchy (JJA/Jenjang Jabatan Akademis) is the reasonof the study. An analysis was performed on the historical data of the university faculty members.Analysis of historical data was done by making use of a data warehouse and data miningapplications to describe and map lecturer’s JJA care, as well as with the data mining tool WEKAversion 3.6.6. to know some of the variables that affect the maintenance of the JJA at BinaNusantara University. Results of this study are most between the ages of 30 and 45 years old, andfor analysis based on a paper having an excellent outcome is the level of lecturer (Lektor) andAssociate Professor. Based on these results, it needs special attention especially those agedbetween 30 and 45 and who have JJA Associate Professor and Lecturer (Lektor).